Perlindungan Hukum terhadap Anak sebagai Korban Eksploitasi Digital di Era Artificial Intelligence - M. Fadel Alfarabi; Ahmad Irzal Fardiansyah; Ria Wierma Putri; Rinaldy Amrullah; Yusdiyanto Yusdiyanto (Jurnal Hukum Lex Generalis, 2026)
The development of digital technology and Artificial Intelligence (AI) has increased the risk of digital exploitation of children, such as misuse of personal data, online sexual exploitation, digital identity manipulation, and the distribution of content harmful to children. This study aims to analyze legal protection for children as victims of digital exploitation and efforts to strengthen regulations in the AI era. The research method used is normative juridical with a legislative and conceptual approach. The results show that legal protection for child victims of digital exploitation has been regulated in at least five main legal instruments, namely the 1945 Constitution of the Republic of Indonesia, Law Number 35 of 2014 concerning Child Protection, Law Number 1 of 2024 concerning Electronic Information and Transactions, Law Number 27 of 2022 concerning Personal Data Protection, and Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. However, these regulations do not specifically accommodate forms of AI-based digital exploitation, particularly related to the use of children's data for the creation of synthetic content, deepfakes and the misuse of digital identity. Therefore, it is necessary to harmonize regulations, establish technical rules regarding child protection in AI-based digital spaces, strengthen supervision of digital platforms, and improve coordination between the government, electronic system providers and child protection agencies to ensure effective legal protection for children as victims of digital exploitation.